Tujuh Belas Akhlaq Pendidik Dalam Pendidikan Islam - Busthomi, Yazidul (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2022)
The seventeen morals of educators in Islamic education are as follows: 1. Accept questions posed by students and be patient with them. 2. Not in a hurry in all matters. 3. Sit with dignity with calm and bow your head. 4. Do not be arrogant to all humans. 5. Prioritizing tawadu' in meeting places and majlis. 6. Not playing and joking. 7. Show affection to students when teaching. 8. Improve stubborn students with good guidance. 9. Do not scold students who are stubborn and do not insinuate them. 10. Not arrogant, not shy and not ashamed to say: "I don't know" or say "wallahu a'lam", if the problem is unclear or unknown. 11. Focus on the questioner and understand the question to answer the problem. 12. Accept the right arguments and listen to them. 13. Submit to the truth by returning to it when guilty. 14. Prohibit students from studying dangerous knowledge. 15. Forbid students from expecting anything other than the pleasure of Allah and the hereafter with useful knowledge. 16. Prevent students from busying themselves with fardhu kifayah before busying themselves with fardhu ain. 17. Prioritizing improving yourself before telling others to do good.